2022
DOI: 10.1017/s1047951122003419
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in childhood: a single-centre experience of 26 years

Abstract: The aim of this study was to present the clinical and microbiological characteristics of patients with infective endocarditis. A retrospective evaluation was made of patients diagnosed with infective endocarditis between 1995 and 2021. The clinical and laboratory characteristics of the patients were recorded together with conditions constituting a risk for the development of endocarditis, treatment, and surgical outcomes. Evaluation was made of 68 patients with a mean age of 7.3 years (3 months–17 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
1
1
1
Order By: Relevance
“…In our study, similar to others, IE was found to be rare in infancy but frequently observed in children older than 2–3 years. The female predominance observed in our analysis contrasts with the similar frequency in male and female patients reported in most studies [ 4 , 5 , 12 ].…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…In our study, similar to others, IE was found to be rare in infancy but frequently observed in children older than 2–3 years. The female predominance observed in our analysis contrasts with the similar frequency in male and female patients reported in most studies [ 4 , 5 , 12 ].…”
Section: Discussioncontrasting
confidence: 95%
“…Delay in the surgical management of these children has led to the emergence of severe complications such as IE before complete surgical repair. Ventricular septal defect was the most common CHD complicated by IE in our study, consistent with findings in most published studies [ 5 , 10 ]. IE exhibits a bimodal distribution with peaks in infancy and adolescence [ 11 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation